Training on the production of instant rhizome-based beverages for inmates of The Class II Women’s Correctional Facility in Malang - Anggi Saputri (Talenta Publisher Universitas Sumatera Utara, 2025)
The Class IIA Malang Women’s Correctional Facility is one of the women’s prisons in East Java Province that experiences overcrowded housing conditions. Nevertheless, various rehabilitation programs continue to be implemented to enhance the self-reliance of inmates, one of which is skills training in the field of food processing. This community service activity aimed to improve the knowledge and skills of inmates in producing instant beverages made from rhizomes as an effort to strengthen their economic independence after release. The methods employed included the delivery of material on the potential of rhizomes as raw materials for instant beverages, as well as hands-on training in product processing. The results of the activity indicated an improvement in the inmates’ skills in processing rhizomes into instant beverage products with market value. These skills are expected to serve as capital for inmates to develop independent businesses and obtain additional sources of income after leaving the correctional facility. Thus, this activity contributes to enhancing human resource capacity and supporting the social and economic reintegration of inmates.